Mathematical Model for the Mexican Coffee Market - Galindo, Gustavo Guerra; Moss, Charles B. (Review of Business Management, 2007)
The assumption that the production of quality coffee is more expensive than the production of coffee of less quality, also that market failures in the transmission of quality signals to producer lower the average quality of coffee produced industry. Used its simultaneous equations in three stage lest square we have found that some variable were significant; the size of the producer affects the share of sold cherry, the quality affects the international green coffee price of México and the quality of cherry increases the share of green coffee sold. But there in no evidence that market power concentration affects the share prices of green coffee. Key-words: Quality. Cherry. Green. Coffee price. Altura. And prima. Size of producer. Market power